Sports injuries patterns in children and adolescents according to their sports participation level, age and maturation - Lara Costa e Silva; Júlia Teles; Isabel Fragoso (BMC, 2022)
Abstract Background Growth can make young athletes more vulnerable to sports injuries. Increased knowledge about injury profile and its predictors is an important part of an overall risk management strategy but few studies have produced information. Methods Information about injury profile and sports participation (SP) level was obtained by LESADO and RAPIL II questionnaires. They were distributed to 651 participants aged between 10 and 18 years attending four schools. Maturity measures were evaluated through maturity offset (MO) and Tanner-Whitehouse III method. Bivariate analysis was used to identify the set of candidate predictors for multinomial logistic regression analysis that was used to determine significant predictors of injury type and body area injury location. Results Regarding injury type predictors recreative boys had more chances of having a sprain or a fracture than a strain. Also, recreative and scholar girls had more chances of having a sprain than a strain. As MO decreased, the chances of girls having a strain or a fracture when compared to sprains were higher. For body area location boys with 10-11 years were more likely to have upper limbs injuries than boys of other ages. This was also confirmed by MO. Spine and trunk injuries were more likely to occur in federate and no sports participation girls. Conclusions Injury type and body area injury location differed significantly by SP level, age group and MO.